Electrospun nanofiber and cryogel of polyvinyl alcohol transdermal patch containing diclofenac sodium: Preparation, characterization and in vitro release studies - Saadon S.; Ansari M.N.M.; Razak S.I.A.; Yusof A.H.M.; Faudzi A.A.M.; Sagadevan S.; Nayan N.H.M.; Anand J.S.; Amin K.A.M. (MDPI, 2023)
cryogel; diclofenac; nanofiber; polymer; polyvinyl alcohol; Article; biocompatibility; chemical interaction; controlled study; drug synthesis; electrospinning; Fourier transform infrared spectroscopy; freeze thawing; gelation; in vitro study; morphology; pharmacological parameters; physical chemistry; scanning electron microscopy; sustained release formulation; thickness